2021
DOI: 10.1093/cvr/cvab013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell metabolic memory causes cardiovascular dysfunction in diabetes

Abstract: Aims  The aim of this study was to identify the molecular mechanism for hyperglycaemia-induced metabolic memory in endothelial cells (ECs), and to show its critical importance to development of cardiovascular dysfunction in diabetes. Methods and results  Hyperglycaemia induces increased nuclear factor-κB (NF-κB) signalling, up-regulation of miR-27a-3p, down-regulation of nuclear factor erythroid-2 related factor 2 (NRF2) expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 56 publications
4
22
0
2
Order By: Relevance
“…В данном контексте сохранение негативного воздействия гипергликемии могло ограничивать протективное влияние РДН в отношении тканей головного мозга. Более того, формирование под влиянием длительно существующей гипергликемии «метаболической памяти» может запускать эффект «домино» в виде прогрессирующего сосудистого повреждения и периваскулярного фиброза [18]. Именно этим феноменом во многом объясняют сохранение высокого риска сердечно-сосудистых осложнений даже при достижении удовлетворительного гликемического контроля.…”
Section: Discussionunclassified
“…В данном контексте сохранение негативного воздействия гипергликемии могло ограничивать протективное влияние РДН в отношении тканей головного мозга. Более того, формирование под влиянием длительно существующей гипергликемии «метаболической памяти» может запускать эффект «домино» в виде прогрессирующего сосудистого повреждения и периваскулярного фиброза [18]. Именно этим феноменом во многом объясняют сохранение высокого риска сердечно-сосудистых осложнений даже при достижении удовлетворительного гликемического контроля.…”
Section: Discussionunclassified
“…These agents mainly function by modifying the properties of cardiac myofilament, rather than altering cytosolic Ca 2+ transients, thus leading to different modulation effects on myocardial relaxation and diastolic tone ( 112 ). Yao et al ( 113 ). demonstrated in endothelial cells hyperglycemia induces a series of changes, which are all memorized by endothelial cells and not erased when switched to a low glucose condition, leading to perivascular fibrosis and cardiac dysfunction.…”
Section: The Regulation Of Endothelial Cells On Cardiomyocytesmentioning
confidence: 99%
“…Moreover, the production of NO, generation of ROS, and the mitochondrial oxygen consumption rate are found similar to the metabolic memory in endothelial cells. In vivo , the disruption of endothelial cell metabolic memory restores cardiovascular function by regulating corresponding signaling pathways in diabetic mice, whereas insulin alone does not improve cardiac function ( 113 ). This regulation on cardiac myocyte function by paracrine of endothelial cells is worth investigating both physiologically and in pathological states ( 112 ).…”
Section: The Regulation Of Endothelial Cells On Cardiomyocytesmentioning
confidence: 99%
“…The accurate mechanisms underlying HbA1c variability-related vascular diseases remain to be illuminated. Several assumptive mechanisms include the release of inflammation [38], oxidative stress [39], impaired endothelial function [40], insulin resistance [41], and metabolic memory [42]. Furthermore, some studies have suggested that HbA1c variability is related to other adverse risk factors, including unhealthy lifestyle behavior (poor diet) [43], irregular compliance to therapy, and multimorbidity [44].…”
Section: Study Id [Ref] the Hr (95 % Ci) Of Hba1c-sd And Vascular Complications Study Outcome Adjustments For Potential Confoundersmentioning
confidence: 99%